Isonitrile-responsive and bioorthogonally removable tetrazine protecting groups. Issue 1 (11th November 2019) - Tu, Julian; Svatunek, Dennis; Parvez, Saba; Eckvahl, Hannah J.; Xu, Minghao; Peterson, Randall T.; Houk, K. N.; Franzini, Raphael M.
Abstract : Tetrazylmethyl groups are reported here as bioorthogonal protecting groups that are readily removed by isonitriles, establishing a valuable addition to the dissociative bioorthogonal chemistry and synthetic methodology toolboxes. Abstract : In vivo compatible reactions have a broad range of possible applications in chemical biology and the pharmaceutical sciences. Here we report tetrazines that can be removed by exposure to isonitriles under very mild conditions. Tetrazylmethyl derivatives are easily accessible protecting groups for amines and phenols. The isonitrile-induced removal is rapid and near-quantitative. Intriguingly, the deprotection is especially effective with (trimethylsilyl)methyl isocyanide, and serum albumin can catalyze the elimination under physiological conditions. NMR and computational studies revealed that an imine-tautomerization step is often rate limiting, and the unexpected cleavage of the Si–C bond accelerates this step in the case with (trimethylsilyl)methyl isocyanide. Tetrazylmethyl-removal is compatible with use on biomacromolecules, in cellular environments, and in living organisms as demonstrated by cytotoxicity experiments and fluorophore-release studies on proteins and in zebrafish embryos. By combining tetrazylmethyl derivatives with previously reported tetrazine-responsive 3-isocyanopropyl groups, it was possible to liberate two fluorophores in vertebrates from a single bioorthogonal reaction. This chemistry will open new opportunities towards applications involving multiplexed release schemes and is a valuable asset to the growing toolbox of bioorthogonal dissociative reactions.